b - Galton, Maurice; Hargreaves, Linda; Comber, Chris; Wall, Debbie (b, 1999)
This book presents the findings of the second round of research, replicating the original ORACLE study, and documents the changes - or lack of them - in primary education and teaching practice over the last twenty years.
Includes bibliographical references and index.
Keywords: z; Elementary school teaching -- Great Britain; Educational change -- Great Britain